(untitled) (Boletín Semillero de Investigación en Familia, 2026)
Introduction: Families shape value formation, identity, and well-being, yet rapid social, economic, and cultural change in Colombian cities such as Villavicencio is reshaping family life, giving rise to new organizational forms and modes of coexistence. This study examines sociodemographic conditions and family organization with attention to housing, health, roles, norms, caregiving, and responses to crisis. Objectives: To analyze the sociodemographic environment and map the diversity of family organizational forms in urban Villavicencio (Meta). Materials and methods: Using a qualitative design informed by Grounded Theory, we employed theoretical sampling and collected data through sociodemographic/ cultural profile surveys and semi structured interviews. Data were processed with office software. Results: Across categories—family finances, housing conditions, traditions, and internal organization—households reported pressures linked to labor insecurity, informality, role reconfiguration, and shifting social norms. Concurrently, families articulated adaptation strategies that reflect resilience, renegotiating values and everyday practices amid change and vulnerability. Conclusion: Social determinants substantially shape living conditions. Family organization is heterogeneous and adaptive, with structures, roles, and practices aligning to local socio-economic contexts; these organizational patterns, in turn, condition intra-family dynamics.